ANALISIS DAN PERANCANGAN SISTEM E-COMMERCE BERBASIS WEB PADA KOPERASI MAHASISWA - R. Iqbal Amirul Insan; Bambang Hariadi; Tan Amelia (Jurnal Sistem Informasi Universitas Dinamika, 2020)
Student Cooperative (Kopma) is a business entity managed by students who offer entrepreneurial experiences to students. The obstacle experienced by Kopma, namely the business scope of Kopma, only covers the college area, limited store area, less strategic location, and the lack of support from the university. Therefore e-commerce is needed as a solution to these problems. E-Commerce was chosen because it can connect Kopma with consumers to make transactions through internet media or other computer networks. The results of the analysis and design is created the Kopma e-commerce analysis and design document. The making of this document is as a reference to the implementation of the system so that the execution is in accordance with the research documents